2018
DOI: 10.1002/chem.201705417
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Novel Type of 2,3′‐BIMs via Platinum‐Catalysed Reaction of Indolylallenes with Indoles

Abstract: Optimisation, scope and mechanism of the platinum‐catalysed addition of indoles to indolylallenes is reported here to give 2,3′‐BIMs with a novel core structure very relevant for pharmaceutical industry. The reaction is modulated by the electronic properties of the substituents on both indoles, with the 2,3′‐BIMs favoured when electron donating groups are present. Although simple at first, a complex mechanism has been uncovered that explains the different behaviour of these systems with platinum when compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 110 publications
0
18
0
Order By: Relevance
“…Taking into account all the experimental evidence, we propose a fast homogeneous Au‐catalyzed 6‐ endo‐trig carbocyclization of the heteroarylallenes to furnish, after protodemetallation, 3 a , the first reaction intermediate observed in the process (Scheme , cycle 1). The intermediate 3 a would then enter into the second catalytic cycle (Scheme , cycle 2), promoted by [Pt‐AuPPh 3 ] homogeneous clusters and aided by Pt‐Au particles in the heterogeneous phase, with the heterobimetallic carbene E as the key intermediate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account all the experimental evidence, we propose a fast homogeneous Au‐catalyzed 6‐ endo‐trig carbocyclization of the heteroarylallenes to furnish, after protodemetallation, 3 a , the first reaction intermediate observed in the process (Scheme , cycle 1). The intermediate 3 a would then enter into the second catalytic cycle (Scheme , cycle 2), promoted by [Pt‐AuPPh 3 ] homogeneous clusters and aided by Pt‐Au particles in the heterogeneous phase, with the heterobimetallic carbene E as the key intermediate.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that Pt is able to promote the 6‐ endo ‐ trig carbocyclization in 1 a , and that 3 and 3′ are true intermediates of the reaction, with Pt‐catalyzed isomerization of 3 to 3′ occurring before the intermolecular nucleophilic addition . Nevertheless, PtCl 2 is not able to promote the carbocyclization of the allenes 1 b – d in an efficient manner under our reaction conditions .…”
Section: Methodsmentioning
confidence: 99%
“…In a different approach, Muñoz & Alonso reported the first tandem process for the platinum catalyzed carbocyclization/nucleophilic addition of N ‐indolylallenes 140 with indoles, accessing the challenging 2,3'‐bisindolylmethane skeleton 141 (Scheme 31a). [ 73 ] This methodology takes one step forward the gold‐catalyzed cyclization of N ‐indolylallenes, that is not able to undergo the intermolecular nucleophilic addition. However, first investigations showed poor conversions and scope limitations with products 142a and 142b (like 96 obtained under gold catalysis, see Scheme 23) obtained as major or only products when deactivated indoles were used.…”
Section: Tandem Reactionsmentioning
confidence: 99%
“…In addition, the generation of the stoichiometric chemical and metallic wastes could cause serious environmental issues, which was not suitable with the development of modern sustainable chemistry. [25][26][27][28][29][30][31][32][33] Bisindolylmethanes (BIMs) and trisindolylmethanes (TIMs) were well reviewed by Shiri et al [34] in 2010, in which they summarized the various approaches to BIMs and TIMs, including 3,3'-BIMs, 2,2'-BIMs, 2,3'-BIMs and TIMs.…”
Section: Introductionmentioning
confidence: 99%